Distribution and genetic diversity of Spodoptera frugiperda J. E. Smith (Noctuidae: Lepidoptera) on maize in West Sumatra, Indonesia - Novri Nelly; Eka Candra Lina; Hasmiandy Hamid; Yunisman Yunisman (Society for Indonesian Biodiversity, 2021)
Abstract. Nelly N, Hamid H, Lina EC, Yunisman. 2021. Distribution and genetic diversity of Spodoptera frugiperda J. E. Smith (Noctuidae: Lepidoptera) on maize in West Sumatra, Indonesia. Biodiversitas 22: 2504-2511. Fall Armyworm (FAW), Spodoptera frugiperda is a major maize pest, reportedly entering West Sumatra, Indonesia in early 2019. After a year of its discovery, there has been no information on the distribution and genetic diversity of this pest. In the present study, research has been carried out to obtain reliable information on the spread, incidence, and genetic diversity of this pest during July-October 2020 at the maize production center of West Sumatra, Indonesia. Sampling was then carried out using the purposive random sampling method, on maize fields in 5 districts (West Pasaman, Padang Pariaman, Solok, Limapuluh Kota and, Tanah Datar). The sample plots were determined with a size of 1x1m2 to observe the population and incidence, meanwhile, the observations were recorded on the larvae number and the percentage damage. Each district location's genetic diversity was analyzed based on the mitochondrial cytochrome c oxidase subunit I (COI) gene nucleotide variations amplified with specific primers. The observations show that S. frugiperda had attacked all maize planting sites in West Sumatra with the attacks ranging percentage from 12.78 to 41.25% and an average larval population of 0.26-1.05 larvae / 2 plants. The genetic diversity analysis results of the S. frugiperda West Sumatra population, on the phylogenetic tree, were divided into two groups, the first is group A which consisted of West Pasaman isolates, and Solok isolates. The second, Group B consisted of Padang Pariaman, Limapuluh Kota, and Tanah Datar isolates (The percentage genetic similirity 99.86-100%). The S. frugiperda population genetics in West Sumatra are similar to those isolates from several other countries in the world.